The Gambia's Political Transition to Democracy: Is Abortion Reform Possible? - Satang Nabaneh (Harvard FXB Center for Health and Human Rights, 2019)
The aim of this paper is to assess The Gambia's laws on abortion. It argues that the restrictive laws on abortion are less a function of religious doctrine and more due to the historical and contemporary structure of the Gambian state, influenced by autocratic rule. As such, the current shift from an authoritarian regime to a democratic one suggests that there may be potential for legal mobilization in the advancement of women's sexual and reproductive rights, including broadening the legal grounds for abortion. In order to achieve the right to safe abortion, the article suggests that a critical mass of support through collaborative networking between parliamentarians, health professionals, human rights activists, the media, and women's rights supporters is needed. Advocacy for expanding the grounds for safe abortion would be premised on international norms and standards, as well as support for research on the magnitude of unsafe abortion and its impact, while addressing the sociocultural context. These different strategies should be adopted to expand access to safe, legal abortion in The Gambia.